Correlative analysis from a phase I clinical trial of intrapleural administration of oncolytic vaccinia virus (Olvi-vec) in patients with malignant pleural mesothelioma - Chintala, Navin K.; Choe, Jennie K.; McGee, Erin; Bellis, Rebecca; Saini, Jasmeen K.; Banerjee, Srijita; Moreira, Andre L.; Zauderer, Marjorie G.; Adusumilli, Prasad S.; Rusch, Valerie W. (Frontiers in Immunology, 2023)
Background The attenuated, genetically engineered vaccinia virus has been shown to be a promising oncolytic virus for the treatment of patients with solid tumors, through both direct cytotoxic and immune-activating effects. Whereas systemically administered oncolytic viruses can be neutralized by pre-existing antibodies, locoregionally administered viruses can infect tumor cells and generate immune responses. We conducted a phase I clinical trial to investigate the safety, feasibility and immune activating effects of intrapleural administration of oncolytic vaccinia virus (NCT01766739). Methods Eighteen patients with malignant pleural effusion due to either malignant pleural mesothelioma or metastatic disease (non-small cell lung cancer or breast cancer) underwent intrapleural administration of the oncolytic vaccinia virus using a dose-escalating method, following drainage of malignant pleural effusion. The primary objective of this trial was to determine a recommended dose of attenuated vaccinia virus. The secondary objectives were to assess feasibility, safety and tolerability; evaluate viral presence in the tumor and serum as well as viral shedding in pleural fluid, sputum, and urine; and evaluate anti-vaccinia virus immune response. Correlative analyses were performed on body fluids, peripheral blood, and tumor specimens obtained from pre- and post-treatment timepoints. Results Treatment with attenuated vaccinia virus at the dose of 1.00E+07 plaque-forming units (PFU) to 6.00E+09 PFU was feasible and safe, with no treatment-associated mortalities or dose-limiting toxicities. Vaccinia virus was detectable in tumor cells 2-5 days post-treatment, and treatment was associated with a decrease in tumor cell density and an increase in immune cell density as assessed by a pathologist blinded to the clinical observations. An increase in both effector (CD8+, NK, cytotoxic cells) and suppressor (Tregs) immune cell populations was observed following treatment. Dendritic cell and neutrophil populations were also increased, and immune effector and immune checkpoint proteins (granzyme B, perforin, PD-1, PD-L1, and PD-L2) and cytokines (IFN-γ, TNF-α, TGFβ1 and RANTES) were upregulated. Conclusion The intrapleural administration of oncolytic vaccinia viral therapy is safe and feasible and generates regional immune response without overt systemic symptoms. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT01766739, identifier NCT01766739.